Plant wastes to biomaterials: toward a circular and sustainable economy - Mohd Razali, Nur Izzati; Johari, Maizatul Akmal; Tahreen, Amina; Barre, Mohamed Soleiman; Ali, Fathilah (Springer, 2024)
Agricultural sector is one of the 3 major sectors that contributes to Malaysian income. Department of statistics Malaysia official portal reported that in 2019, agriculture contributed 7.29% of gross domestic product (GDP).